2014
DOI: 10.1002/mds.25809
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cortical plasticity and GABAergic modulation in essential tremor

Abstract: Essential tremor (ET) is the most common movement disorder among adults. Cerebellar dysfunction is thought to be involved in the pathogenesis of ET; however, imaging, electrophysiological studies, and clinical observations have suggested that the cerebral cortex also may participate. We sought to investigate the possible motor cortical contribution to ET by assessing response to continuous theta-burst stimulation (cTBS), a recognized tool that can produce transient plastic changes, in the primary motor and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…Therefore, the findings of the previous study [31] do not allow the general conclusion that M1 plasticity is normal in ET. Another study that applied continuous theta-burst stimulation, a protocol that in healthy subjects leads to a long-term depression (LTD)-like decrease in MEP amplitude [34], demonstrated a lack of this type of LTD-like plasticity in ET patients [35]. The current data support the notion that M1 plasticity is impaired in ET patients with intention tremor.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, the findings of the previous study [31] do not allow the general conclusion that M1 plasticity is normal in ET. Another study that applied continuous theta-burst stimulation, a protocol that in healthy subjects leads to a long-term depression (LTD)-like decrease in MEP amplitude [34], demonstrated a lack of this type of LTD-like plasticity in ET patients [35]. The current data support the notion that M1 plasticity is impaired in ET patients with intention tremor.…”
Section: Discussionsupporting
confidence: 76%
“…Application of cTBS to M1 and other brain areas has been used to measure abnormalities in cortical plasticity and to assess therapeutic responses to interventions aimed at restoring normal cortical plasticity in several neurological and psychiatric disorders, including Alzheimer’s disease (Freitas et al, 2011a), autism spectrum disorders and fragile X syndrome (Oberman et al, 2010, 2012, 2014, 2016), dementia (Cantone et al, 2014), epilepsy (Carrette et al, 2016), essential tremor (Chuang et al, 2014), hemispatial neglect (Cazzoli et al, 2012; Koch et al, 2012), major depression (Li et al, 2014), multiple sclerosis (Mori et al, 2013), obsessive-compulsive disorders (Wu et al, 2010; Suppa et al, 2014), Parkinson’s disease (Koch et al, 2009), schizophrenia (Poulet et al, 2009; Eberle et al, 2010; McClintock et al, 2011), stroke (Ackerley et al, 2010; Hsu et al, 2012; Di Lazzaro et al, 2013, 2016), tinnitus (Forogh et al, 2014), and Tourette syndrome (Suppa et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies focusing on the potential role for primary motor cortex (M1) within the central oscillatory network in ET demonstrated that unilateral continuous theta burst stimulation (cTBS) of M1 cortex improves tremor in ET patients [44]. When compared to DBS, superficial cortical stimulation is less complex to perform and has a lower incidence of cerebral haemorrhage.…”
Section: Disease; Kinetic Tremormentioning
confidence: 99%